INCREASING LEARNING RESULTS STUDENTS OF ELEMENTARY SCHOOL THROUGH TEAMS GAMES TOURNAMENT LEARNING - Witarsa, Ramdhan; Indriastuti, Yosi; Fitriani, Fini; Suhartini, Ai Tintin; Rosmaya, Andriyanti; Mulyati, Siti Sri (COLLASE (Creative of Learning Students Elementary Education), 2018)
The purpose of the implementation of Classroom Action Research (CAR) is to improve the learning outcomes of science materials in the Human Senses SDN Ciampel. The implementation of CAR is done through two cycles where each cycle consists of four stages: (1) planning, (2) implementation of action, (3) observation, and (4) reflection. Data collection techniques are done at the end of the cycle using tests, observations, and documentation. The success indicator of this CAR is the learning outcomes of learners who achieve the Minimum Exhaustiveness Criteria (MEC) is greater than 60 as many as 80% of learners, as well as the appearance of teachers in learning above the score 80. Results of research obtained from the assessment of learning outcomes of learners class IV in cycle I that is: average class 51,95; with mastery learners learn 69,56%; the value of teacher performance 88.07%. Learning outcomes in cycle II are: average class 77.83; with learners learning completeness 91,30%; the value of the teacher's appearance is 91.20%. The conclusion of this research is that the learning of TGT can improve the science learning result of the students of the human sense tool material in the fourth grade students and can improve the performance of teachers in the learning at SDN Ciampel.